The spirit and the song: pneumatological reflections on popular music - Green, Chris E. W.; Félix-Jäger, Steven (Theology, religion, and pop culture, 2024)
"This book considers how music can transport listeners beyond themselves. Both music and the Spirit operate between languages and cultures, between desires and longings, between the visible and invisible, and between the deep and near. Thus, the Spirit, through music, unites and gathers communities, revealing new possibilities"--